Action of colloidal solution of copper and zinc on seed germination of oats - Гончар, Л. М. (Scientific Progress & Innovations, 2016)
The article shows results of impact colloidal solution of various concentrations of zinc, copper and their complex on laboratory germination of oats’ seeds. We established that effect of copper in concentration 1:1 is phytotoxic for germination of oats’ seeds. We noted, that copper concentration 1:1 had reduced seed germination for 3–14 %, which has a negative impact on subsequent processes of growth oats. Concentration of copper 1:10 was affecting on germination of seeds at the same level as control variant, so it is not evident phytotoxicity of copper in that solution concentration. So it has the question about reasonableness of using that concentration of solution. We established, that with copper concentration 1:100 seeds germination of all surveyed crops was increased, what allow argue about the effectiveness of solution at this concentration. Germination of oats’ seeds was reduced with zinc concentrations 1:1 and 1:10, only with concentration 1:100 we observed growing of percent similar seeds.